Legislation for coal mining companies in Colombia, its social and environmental effects (2014)
The present document aim to show several aspects that relates government legislation such as Colombian with the international standards; address the growing economic activity from coal industry beyond the financial scenario. Such that are illustrated from the contravention of existing regulations, at the level of environmental consequences derived from exploration and exploitation by multinationals, also the violation of human rights in areas such as work, health, right to life and dignity, healthy environment and heritage communities affectation are shown. Finally, proposals are made to reform the national and international standard for its application be beneficial in all areas, as well as the recommendation to businesses of raise awareness that objectives that positively affect not only their pockets, but also the environment and the community.